The HD-ZIP IV transcription factor Tril regulates fruit spine density through gene dosage effects in cucumber. (25th July 2020) - Du, Hui; Wang, Gang; Pan, Jian; Chen, Yue; Xiao, Tingting; Zhang, Leyu; Zhang, Keyan; Wen, Haifan; Xiong, Liangrong; Yu, Yao; He, Huanle; Pan, Junsong; et al.
Abstract : The HD-ZIP IV transcription factor Tril regulates fruit spine density through gene dosage effects in cucumber and functions upstream of the negative regulator NS with respect to spine initiation. Abstract: Trichomes and fruit spines are important traits that directly affect the appearance quality and commercial value of cucumber ( Cucumis sativus ). Tril ( Trichome-less ), encodes a HD-Zip IV transcription factor that plays a crucial role in the initiation of trichomes and fruit spines, but little is known about the details of the regulatory mechanisms involved. In this study, analysis of tissue expression patterns indicated that Tril is expressed and functions in the early stages of organ initiation and development. Expression of Tril under the control of its own promoter (the TrilPro::Tril-3*flag fragment) could partly rescue the mutant phenotypes of tril, csgl3 ( cucumber glabrous 3, an allelic mutant of tril ), and fs1 ( few spines 1, a fragment substitution in the Tril promoter region), providing further evidence that Tril is responsible for the initiation of trichomes and fruit spines. In lines with dense spine, fs1 -type lines, and transgenic lines of different backgrounds containing the TrilPro::Tril-3*flag foreign fragment, spine density increased in conjunction with increases in Tril expression, indicating that Tril has a gene dosage effect on fruit spine density in cucumber. Numerous Spines ( NS ) is a negative regulatory factor of fruit spine density. Characterization of the molecular and genetic interaction between Tril and NS/ns demonstrated that Tril functions upstream of NS with respect to spine initiation. Overall, our results reveal a novel regulatory mechanism governing the effect of Tril on fruit spine development, and provide a reference for future work on breeding for physical quality in cucumber.